2019
DOI: 10.1021/acs.jced.9b00304
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine-Immobilized Montmorillonite: An Efficient Adsorbent for Removal of Pb2+ and Cu2+ from Aqueous Solution

Abstract: Herein, a new effective material, tyrosine-functionalized montmorillonite (Tyr-Mt), was prepared and used in the adsorption of Pb 2+ and Cu 2+ ions. Tyr-Mt is synthesized by modifying sodium montmorillonite (Na-Mt) with L-tyrosine. The X-ray diffraction, ζ-potential, Fourier transform infrared spectroscopy, Brunauer−Emmett−Teller, and thermal analysis results showed that the modifier was successfully inserted into the interlayer of montmorillonite. In single-ion systems, various parameters were thoroughly eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The interlayer reaction of Sr/Cs with EPS-MMT was consistent with the results of adsorption isotherms described with Langmuir and Freundlich models. A similar phenomenon was reported by Chu et al on tyrosine adsorption on MMT.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The interlayer reaction of Sr/Cs with EPS-MMT was consistent with the results of adsorption isotherms described with Langmuir and Freundlich models. A similar phenomenon was reported by Chu et al on tyrosine adsorption on MMT.…”
Section: Resultssupporting
confidence: 88%
“…Notably, after adsorbing Sr, the characteristic peak became sharper and more obvious with an increasing loading, suggesting a more ordered feature of the composite . This confirmed the interlayer reaction of Sr with EPS . Conversely, the characteristic peak began to weaken after adsorbing Cs, almost disappearing after absorbing 1000 mg/L Cs, demonstrating a disordered feature formation or the collapsing of interlayers. ,, On the one hand, there should be the presence of substances with an amorphous structure and/or the formation of a disordered pillared structure, which was confirmed by SEM characterization (discussed below, Figure a,f), and was consistent with the basal spacing.…”
Section: Resultsmentioning
confidence: 52%
“…Recently, Tyrosine immobilized montmorillonite was employed as an adsorbent for removal of inorganic metal ions, Pb 2+ and Cu 2+ and results proved an excellent performance of adsorbent for metal ion decontamination. (Chu et al 2019). Similarly, L-Cysteine modified montmorillonite alginate nanocomposite was used as an adsorbent for the removal of Ni 2+ , Pb 2+ and Cu 2+ and satisfactory results were reported (Mittal et al 2016).…”
Section: Introductionmentioning
confidence: 96%
“…In particular, the elimination of Cu 2+ adsorption process can provide additional technical and economic benefits. Therefore, it is necessary to study the application of novel adsorbents to consolidate their industrial application [11][12][13]. In this direction, it has been reported that two-dimensional (2D) nanomaterials show potential as promising adsorbents for heavy metal removal [14][15][16].…”
Section: Introductionmentioning
confidence: 99%